2021
DOI: 10.1016/j.tust.2021.103838
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of long-term deformation of a tunnel in soft rock by utilizing particle swarm optimized neural network

Abstract: The continuous monitoring of long-term performance of tunnels constructed in soft rock masses shows that the rock mass deformations continue after construction, albeit at a rate that reduces with time. This is in contrast with NATM postulates which assume deformation stabilizes shortly after tunnel construction. This paper proposes the prediction of long-term vertical settlement performance of a tunnel in soft rock mass, through the inclusion of a Burger's creep viscous-plastic constitutive law to model post-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Applying Burger's model to FEM, Fahimifar et al [11] studied the analytical solution of a viscoelastic circular tunnel under hydrostatic pressure. Meho et al [13] evaluated the long-term deformation characteristics of soft rock in an efficient way by using an improved Burger's model in finite element neural network simulation, and the results agree well with the experimental results. Then, applying Burger's model into DEM, Li et al [14] studied the rheological behavior of soft rock; Guo et al [15] studied the time-dependent mechanics of sandstone.…”
Section: Introductionmentioning
confidence: 70%
“…Applying Burger's model to FEM, Fahimifar et al [11] studied the analytical solution of a viscoelastic circular tunnel under hydrostatic pressure. Meho et al [13] evaluated the long-term deformation characteristics of soft rock in an efficient way by using an improved Burger's model in finite element neural network simulation, and the results agree well with the experimental results. Then, applying Burger's model into DEM, Li et al [14] studied the rheological behavior of soft rock; Guo et al [15] studied the time-dependent mechanics of sandstone.…”
Section: Introductionmentioning
confidence: 70%
“…A significant number of engineering applications and laboratory studies indicated the mechanical response related to weak and soft rock's time-dependent behavior is relatively complicated (Zhu et al 2020;Yan et al 2020;To ¨ro ¨k et al 2019;Singh et al 2018;Patil et al 2018;Vlastelica et al 2018;Lyu et al 2017;Gu ¨nther et al 2015; Mis ˇc ˇevic ´and Vlastelica 2014; Zhou et al 2014). One of the significant parameters affecting the underground spaces' longterm stability is weak rock mass creep response (Kovac ˇevic ´et al 2021;Panthi and Shrestha 2018). In addition, underground water as an important environmental component influences weak rock's short-term and long-term behavior, especially in fault and karst regions (Verbovs ˇek and Kanduc ˇ2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al (2021) found that tunnel-collapse accidents caused by improper control of the surrounding rock stress release, high ground stress, and discontinuity often occur in the construction process of soft rock tunnels, causing significant losses to the corresponding projects. A Kovacevic et al (2021) and Cheng et al (2018) found that to ensure the construction safety in a soft rock tunnel with high geo-stress and the stability and durability of the tunnel, it is necessary to initially study the deformation laws of the rock mass. At present, the control and monitoring processes for tunnel rock mass deformations are mainly concentrated on the surrounding rock of the excavated part.…”
Section: Introductionmentioning
confidence: 99%